Wavelength-dispersive spectroscopy in the hard x-ray regime of a heavy highly-charged ion: the 1s Lamb shift in hydrogen-like gold. (18th July 2018) - Gassner, T; Trassinelli, M; Heß, R; Spillmann, U; Banaś, D; Blumenhagen, K-H; Bosch, F; Brandau, C; Chen, W; Dimopoulou, Chr; Förster, E; Grisenti, R E; et al.
Abstract: Accurate spectroscopy of highly-charged high- Z ions in a storage ring is demonstrated to be feasible by the use of specially adapted crystal optics. The method has been applied for the measurement of the 1 s Lamb shift in hydrogen-like gold (Au +78 ) in a storage ring through spectroscopy of the Lyman x-rays. This measurement represents the first result obtained for a high- Z element using high-resolution wavelength-dispersive spectroscopy in the hard x-ray regime, paving the way for sensitivity to higher-order QED effects.